ANALYSIS OF PRODUCTION AND INCOME OF AMBON BANANA FARMING IN SECANGGANG DISTRICT, LANGKAT REGENCY - Adriansyah Yoesoef; Faisal Azhari Baldan Panjaitan; Aadil Hussain Mir (CV. Radja Publika, 2023)
This study aims to analyze the production levels, costs, revenues, and income of Ambon banana farming in Secanggang District , Langkat Regency . The research method used is a quantitative approach with descriptive and analytical methods. The data used consists of primary data obtained through direct interviews with farmers using questionnaires, as well as secondary data from related agencies. Data analysis was carried out by calculating production costs, revenues, income, and business feasibility using the R/C Ratio. The results of the study indicate that the average production of Ambon bananas reaches 12,000 kg per hectare per period with an average selling price of Rp3,500 per kg. Total production costs incurred are Rp17,500,000 per hectare per period, while revenue is Rp42,000,000 and income is Rp24,500,000. The results of the business feasibility analysis show a R/C Ratio value of 2.40, which means this farming business is feasible and profitable to develop. Overall, Ambon banana farming has good prospects for increasing farmers' income, but efforts are still needed to improve production efficiency and price stability.